Predominant Biphenyl Dioxygenase From Legacy Polychlorinated Biphenyl (PCB)-Contaminated Soil Is a Part of Unusual Gene Cluster and Transforms Flavone and Flavanone - Suman, Jachym; Strejcek, Michal; Zubrova, Andrea; Capek, Jan; Wald, Jiri; Michalikova, Klara; Hradilova, Miluse; Sredlova, Kamila; Semerad, Jaroslav; Cajthaml, Tomas; Uhlik, Ondrej (Frontiers in Microbiology, 2021)
In this study, the diversity of bphA genes was assessed in a 13C-enriched metagenome upon stable isotope probing (SIP) of microbial populations in legacy PCB-contaminated soil with 13C-biphenyl (BP). In total, 13 bphA sequence variants (SV) were identified in the final amplicon dataset. Of these, one SV comprised 59% of all sequences, and when it was translated into a protein sequence, it exhibited 87%, 77.4%, and 76.7% identity to its homologues from Pseudomonas furukawaii KF707, Cupriavidus sp. WS, and Pseudomonas alcaliphila B-367, respectively. This same BphA sequence also contained unusual amino acid residues, Alanine, Valine, and Serine in region III, which was reported to be crucial for the substrate specificity of the corresponding biphenyl dioxygenase (BPDO), and was accordingly designated BphA_AVS. The DNA locus of 18 kbp containing the BphA_AVS-coding sequence retrieved from the metagenome was comprised of 16 ORFs and was most likely borne by Paraburkholderia sp. The BPDO corresponding to bphAE_AVS was cloned and heterologously expressed in E. coli, and its substrate specificity toward PCBs and a spectrum of flavonoids was assessed. Although depleting a rather narrow spectrum of PCB congeners, the efficient transformation of flavone and flavanone was demonstrated through dihydroxylation of the B-ring of the molecules. The homology-based functional assignment of the putative proteins encoded by the rest of ORFs in the AVS region suggests their potential involvement in the transformation of aromatic compounds, such as flavonoids. In conclusion, this study contributes to the body of information on the involvement of soil-borne BPDOs in the metabolism of flavonoid compounds, and our paper provides a more advanced context for understanding the interactions between plants, microbes and anthropogenic compounds in the soil.